A Process Evaluation of a Performance Psychology Intervention for Transitioning Elite and Elite Musicians - Kegelaers, Jolan; Oudejans, Raôul R. D. (Frontiers in Psychology, 2020)
The present study presents a process evaluation of a performance psychology intervention for transitioning elite and elite musicians. The goal of the intervention was to provide participants with an amalgamation of evidence-informed principles, aimed to improve their quality of practice and performance preparation. The intervention consisted of an educational session followed by four workshops. In total, eight transitioning elite and seven elite musicians participated. Process measures included quantitative and qualitative workshop evaluations, monitoring logs, and semi-structured interviews. Overall, the intervention was evaluated positively by the participants. However, differences were present between the groups, with the elite musicians typically evaluating the intervention more favourably compared to the transitioning elites. Specific positive outcomes included an increased awareness and re-examining of current practice strategies, more structured and goal-directed practice, increased practice efficiency and focus, a more proactive approach to performances, and increased attention for the physical aspects of playing. Moreover, a number of contextual considerations and implementation challenges became evident. Important implications for performance psychology interventions and practitioners in music are discussed.